2016
DOI: 10.4102/jef.v9i3.67
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of internal ta compliance costs: Evidence from South Africa

Abstract: Being tax compliant generates costs and these costs affect small business tax compliance behaviour and contribution. This study uses multiple regression analyses to investigate the key drivers of small business's internal tax compliance costs (hours spent internally on tax compliance activities). This will assist Revenue Services in understanding what factors (determinants) could increase a small business's internal tax compliance costs and might assist in managing tax compliance behaviour and contribution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
5
1
1
Order By: Relevance
“…In a recent study, it was confirmed that with the current provisions for Turnover Tax in place small businesses carry a higher proportionate burden in respect of tax and employees' compliance activities (Smulders et al 2016). This confirms that the Government will have to relook at innovative ways to reduce compliance costs of microbusiness in order to encourage growth that will stimulate employment and assist the Government with South Africa's high unemployment rate.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a recent study, it was confirmed that with the current provisions for Turnover Tax in place small businesses carry a higher proportionate burden in respect of tax and employees' compliance activities (Smulders et al 2016). This confirms that the Government will have to relook at innovative ways to reduce compliance costs of microbusiness in order to encourage growth that will stimulate employment and assist the Government with South Africa's high unemployment rate.…”
Section: Discussionmentioning
confidence: 86%
“…The South African Revenue Service (SARS) (2008) reported that many small businesses do not pay tax as they are overwhelmed by the complexities of the current tax system and high compliance cost, and this was confirmed in later research (Smulders et al 2016).…”
Section: Introductionmentioning
confidence: 85%
“…An increase in turnover is normally associated with an increase in transaction documents, which should be presented to tax officials as a proof. This increase in tax compliance costs because of record-keeping should be very marginal and is not expected to significantly affect tax compliance costs, contrary to the findings by Smulders et al (2016) and Yesegat (2009). Considering these findings from previous studies, the following hypotheses in relation to business size were formulated:…”
Section: Size Of Businessmentioning
confidence: 96%
“…The construction industry was selected and used as a unit of analysis. Studies carried out by Pope and Abdul-Jabbar (2008), Coolidge (2012), Hansford and Hasseldine (2012), Lignier and Evans (2012) and Smulders et al (2016) attempted to determine factors driving tax compliance costs, but did not differentiate between sectors of the economy. There was an implied assumption that small businesses in different sectors have similar levels of ability to deal with tax issues and that they incur tax compliance costs similarly across the board.…”
Section: Introductionmentioning
confidence: 99%
“…Esta influencia se puede explicar en el contexto de un mercado formal que establece reglas para el funcionamiento de la mype, dichas reglas son de cumplimiento forzoso y a la vez la base de las interacciones entre la mype y los reguladores, es decir, la existencia formal de la mype, radica en el cumplimiento de las reglas establecidas por el regulador, sin lo cual, se haría más difícil cumplir con sus objetivos de gestión. La dificultad de las interacciones myperegulador se da en el hecho que desde la perspectiva de la mype las interacciones con el regulador (determinadas por las normas establecidas) no aportan al cumplimiento de sus objetivos de gestión y por DOI: http://dx.doi.org/10.17268/sciendo.2023.023 tanto no hay incentivo para cumplirlas (Smulders et al, 2016). Por otro lado, el regulador exige el cumplimiento de las normas ya que desde su perspectiva el cumplimiento de las normas permite mejorar la competitividad, acceder a más clientes y tener mejores ingresos, con la posibilidad de acceder a fuentes de financiamiento (Rand y Torm, 2012), con lo cual, la mype si podría cumplir sus objetivos de gestión.…”
Section: Modelo Teóricounclassified